Hubungan Keterampilan Memparafrasakan Puisi dengan Keterampilan Menulis Naskah Drama pada Siswa Kelas XI SMAN 9 Kota Bogor - Tri Mahajani; Adinda Masri Putri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, UNPAK, 2021)
This study aims to determine the correlation between poetry paraphrasing skills and drama script writing skills in class XI students of SMAN 9 Bogor City. The method for this study is a quantitative with correlation techniques. The population in this study were all students of class XI of SMAN 9 Bogor with a total of 310 students. Writing drama scripts by collecting data through poetry paraphrasing skilltests is the technique of the sample which 36 students from class XI IPS 3 as the object of this study. The research hypothesis has a positive relationship between poetry paraphrasing skills and drama script writing skills. After the data was collected, the researcher calculates it by the product moment formula. Based on the theoretical (r) coefficient or r table in the product moment correlation table, it can be seen that the significant level of 5% and 1% of (N = 36) respectivelyare 0.329 and 0.424. The results show rabel (5% = 0.329) less than rxy (0.331) less thanrabel (1% = 0.424) which means that it relates to a positive relationship between the skills of paraphrasing variable (X) with drama script function variable (Y) by weak level. Thus poetry parenting skills contributed 33% to drama script writing skills. While the other 67% is influenced by other variables not examined in this study.